DETERMINAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS PEJUANG KOTA BEKASI TAHUN 2020-2021 - Annisa Tsabitah Salsabila (2021)
Pneumonia is one of the unresolved problems in Indonesia, especially pneumonia in toddlers.. Therefore, this study aims to find out the determinants of pneumonia incidences in toddlers in the working area of Puskesmas (Community Health Center) Pejuang Bekasi City. The method used was analytic with a case-control design. The sampling technique used purposive sampling. The samples were 126 respondents using a sample ratio of 1: 2 for the case group and control group. The data source of the study was secondary data from medical records of patients and primary data according to the results of interviews using online questionnaires. Data analysis used a chi-square test and multiple logistic regression. The variables studied were the education of the mother, birth weight, exclusive breastfeeding, vaccination status, administration of vitamin A, cigarette smoke exposure in the house, the use of mosquito coils, type of fuel, type of house wall, and type of house floor. The results of the study show that factors regarding pneumonia incidences in toddlers are the education of mother (p-value=0.002; OR= 4.630), birth weight (p-value= 0.000; OR=5.846), vaccination status (p-value= 0.004; OR=3.714), administration of vitamin A (p-value=0.012; OR= 3.800), cigarette smoke exposure in the house (p-value= 0.001; OR= 5.826), and the use of mosquito coils (p-value= 0.001; OR=7.097). Based on the results of multivariate analysis, the most influential factor is cigarette smoke exposure in the house (OR=4,298; 95%CI=1,419-13,022) after being controlled by variables of birth weight, administration of vitamin A, and use of mosquito coils. Thus, it is suggested for mothers who have toddlers to provide complete vaccination, administration of vitamin A, avoid cigarette smoke exposure in the house, and replace the use of mosquito coils as one of the efforts to prevent pneumonia.